Rotulagem ambiental e desenvolvimento sustentável: responsabilidade socioambiental das empresas - Cartaxo, Beatriz Rolim (2017)
Nowadays, corporate strategies are based on the search for mechanisms to communicate their actions and visions regarding social and environmental responsibility in order to add value and credibility to their brand, highlighting, in this sense, environmental labeling. The objective of this study is to analyze environmental labeling in environmental development through the study of the company's crisis, ethics and socio and environmental responsibility, as well as the labeling process and how sustainability is achieved. The choice of subject is justified due to its repercussion in the current society that, little by little, has come to realize that the world is actually experiencing an environmental crisis that jeopardizes the survival of all who inhabit Planet Earth. Through a bibliographical survey, it can be observed that, due to the great environmental problems and the concern with the recovery of the nature, many actions and practices are being promoted for an environmental improvement, since the concern with the environmental degradation increased significantly, and to mobilize practices from ideas to solutions that will help mitigate damages that are so damaging to nature has become a priority. It can be seen that, given the concern, sensitivity and awareness of the problems of preservation as well as the fact that increasing investments are being made in ecological management and the acquisition of products that do not harm the environment, companies are, more and more, winning environmental certifications. Therefore, this will result in a strengthening of the company's image, proving that it is compatible to insert ethics in the values of economic efficiency, in the sense of social justice desired by the national legal system.